Vers l’image aveugle : George Oppen et l’usage de la lumière - Xavier Kalck (Sillages Critiques)
This article means to discuss the question of light in George Oppen’s poetry, quite independently of the images built within the poems. It is a paradoxical endeavour, and should only be seen as an exercise in approaching such an otherwise concrete poetry, known for its emphasis on the visible world. Yet, let us assume there is some merit to this detour, inasmuch as it will allow us to show how eminently reflexive and abstract George Oppen’s poetry is, and that it ought not to be read only when in search of serial and local perceptions.